Case Report: Bilateral lens dislocation as an atypical presentation of acromegaly and review of the ocular effects of GH/IGF-1 excess - Vitale, Laura; Fatti, Letizia Maria; Bonomi, Marco; Frara, Stefano; Vitale, Giovanni; Persani, Luca; Cangiano, Biagio (Frontiers in Endocrinology, 2025)
IntroductionWe report the case of a 71-year-old woman with acromegalic facies, referred following bilateral idiopathic lens luxation (LL). Subsequent investigations revealed a 15-mm pituitary adenoma, along with biochemical evidence of massive growth hormone hypersecretion (Growth Hormone (GH): 93.22 µg/L; insulin-like growth factor 1 [IGF-1]: 748 µg/L), consistent with acromegaly. She exhibited multiple comorbidities, including arterial hypertension, chronic heart failure secondary to dilated cardiomyopathy—compatible with acromegalic heart disease (AHD)—osteoporosis, and type 2 diabetes mellitus (T2DM), reflecting a long-standing and high-burden disease.Treatment and clinical courseSince the patient was not eligible for surgery and daily subcutaneous injections were unfeasible due to the patient’s lack of autonomy and limited caregiver support, therapy with lanreotide was initiated despite complete resistance to high doses of the classic analogue. We switched to pasireotide, achieving excellent disease control with 60 mg administered every 28 days. Progressive reduction in IGF-1 levels subsequently allowed a dose tapering to 40 mg every 28 days. Biochemical control of acromegaly was accompanied by improvement in disease-related complications (most notably T2DM), as well as the development of secondary hypocortisolism.Ocular complicationsBilateral lens dislocation is not a known acromegaly complication; however, its bilateral occurrence suggests an underlying systemic cause. A plausible pathogenetic mechanism may involve chronic GH hypersecretion and IGF-1 overexpression, with subsequent interaction with ocular receptors. IGF-1 exerts an antiapoptotic and pro-proliferative action on lenticular cells through interaction with the IGF-1 receptor and the intracellular PI3K/Akt pathway. It is a regulatory factor in the synthesis and degradation of fibrillin-1, a glycoprotein abundantly expressed in the extracellular matrix of the ciliary zonule, whose altered synthesis may underlie weakness of the lens suspensory apparatus. This is the first reported case of its genre, although bilateral intraocular lens subluxation (LS) in a patient with acromegaly and elevated intraocular pressure has previously been reported.ConclusionsBilateral lens dislocation may represent an atypical presentation of acromegaly. It may indicate advanced disease and, if confirmed in other cohorts, could be considered among the suggestive signs of acromegaly. In our case, the use of pasireotide allowed adherence to therapy and optimal therapeutic response in a multicomplicated, non-self-sufficient patient.